Diseño a través de la música como instrumento para reforzar y trabajar la motricidad fina en estudiantes con Síndrome de Down de la fundación AMADEUS. (2022)
100% of people with Down syndrome have hypotonia or low muscle tone. This condition causes people with Down syndrome to have poor fine motor skills. Fine motor activities are those that mostly require a visual-manual relationship. For the rehabilitation of muscle tone, music has shown to have good results in the students of the AMADEUS Foundation. The purpose of the project is therefore to work and strengthen the fine motor skills of people with Down Syndrome at the AMADEUS Foundation through music through design.